Anti-fungal activity of Ardisia crispa (Thunb.) A.DC. against several fungi responsible for athlete's foot - Somchit, Muhammad Nazrul; Adam, Yunus; Yee, Hee Chong; Ahmad, Zuraini; Abdul Kadir, Arifah; Zakaria, Zainul Amiruddin (Academic Journals, 2011)
The body normally hosts a variety of saprotrophic micro-organisms that may cause infection. Athlete's foot causes scaling, flaking and itching of the affected skin. Blisters and cracked skin may also occur, leading to exposed raw tissue, pain, swelling and inflammation. Secondary bacterial infection can accompany the fungal infection. This work examined the anti-fungal activity of Ardisia crispa (AC) against common fungi that cause Athlete's foot and several other pathogenic fungi. The antimicrobial activity of water, ethanol and chloroform extracts of AC was tested against fungal strains using the disc diffusion method. This antimicrobial activity was compared to standard antifungal drugs (griseofulvin, fluconazole and itraconazole). Results revealed that chloroform extract of AC had potent anti-fungal activity against Trichophyton rubrum ATCC 40051 and Trichophyton mentagrophytes ATCC 40004 which are the two most commonly cause of Athlete's foot. Moderate activity was observed against Candida albicans ATCC 14053, Candida tropicalis ATCC 14056, Microsporum canis (clinical isolates and identified at the Department of Pathology and Microbiology, Universiti Putra Malaysia) and Aspergillus fumigatus ATCC 14109. The ethanol extract only had mild activity against the Candidia spp and the water extract was devoid of any activity. The anti-fungal activity of chloroform extract was statistically more potent than griseofulvin but less potent than fluconazole and itraconazole. Findings from current study support the use of AC in traditional medicine for the treatment of various fungal infections and may potentially be used in the treatment of athlete's foot.